Media Pembelajaran Komik Edukatif Digital untuk Meningkatkan Kemampuan Menyelesaikan Soal Pecahan Matematika di Kelas IV Madrasah Ibtidaiyah - Auffah Yumni; Yuli Deliyanti (Lembaga Yasin AlSys, 2026)
Students’ low ability to solve fraction problems and the limited availability of learning resources that are attractive and easy to understand in mathematics learning constitute an important basis for developing creative and dynamic learning media. This study aims to develop and test the validity, practicality, and effectiveness of digital educational comic media in improving Grade IV students’ ability to solve mathematical fraction problems. This study used a Research and Development (R&D) approach with the ADDIE development model. The research subjects consisted of 25 Grade IV students at MIN 12 Kota Medan. Data were collected through observation, interviews, questionnaires, expert validation, and tests in the form of pretests and posttests, and were then analyzed using percentages and N-Gain. The validation results showed that the digital educational comic media obtained an average score of 88.6%, categorized as highly valid. The practicality test results obtained an average score of 87.43%, categorized as highly practical. Furthermore, the effectiveness test results showed an N-Gain value of 79%, which falls into the high category, indicating that digital comic-based learning media are effective in improving students’ ability to solve mathematical fraction problems. The conclusion of this study affirms that digital educational comic media are feasible, practical, and effective for use as alternative mathematics learning media on fraction material. The implications of this study indicate that students can use digital educational comic media independently or in structured learning to strengthen their understanding of fraction concepts and improve learning motivation, while further research can test the effectiveness of the media over a longer period or on other mathematics topics.